Europa między demokracją i zaściankiem - Paradowski, Ryszard (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
In the period when ‘our natural political environment’ was provided by controlled ‘socialist democracy’ we tended to look to Europe for a model of democratic perfection. As the doctrine of human rights and the institutions guarding it became increasingly common, this conviction was yet augmented. Such a high opinion of European political practice was undoubtedly affected by the defeat of Nazism, which was commonly interpreted as a victory for democracy. The feeling of European democratic identity was further confirmed several decades later, when Communism collapsed. Thus the process of progressive European integration, which commenced soon after the end ofWorldWar II, and intensified after 1989, seemed to testify to Europe’s unanimously democratic nature. Yet a more considerate insight into the unification processes raises numerous doubts as to whether we are really facing the construction of European structures following the principles of liberal democracy.